Yokoyama procedure for esotropia associated with high myopia: real‐world data from a large‐scale multicentre analysis. Issue 8 (2nd March 2021) - Wabbels, Bettina; Fricke, Julia; Schittkowski, Michael; Gräf, Michael; Lorenz, Birgit; Bau, Viktoria; Nentwich, Martin M.; Atili, Abed; Eckstein, Anja; Sturm, Veit; Beisse, Christina; Sterker, Ina; et al.
Abstract: Purpose: High myopic patients may develop strabismus due to globe dislocation out of the normal extraocular muscle cone. Surgical correction of this strabismus type is possible by joining the superior and lateral rectus muscles without the need for a scleral suture called the Yokoyama procedure. Data from large patient samples and the evaluation of a potential effect of an additional medial rectus recession (MRR) have been lacking so far. Methods: We pooled retrospective patient data of 14 departments of ophthalmology in Germany and Switzerland and analysed determinants of postoperative results using multivariable regression models. Results: We included 133 patients (mean age: 59.7 ± 13.4 years, surgery between 2008 and 2017) with a mean preoperative esotropia (both Yokoyama with and without MRR) of 23.8°±4.6°. The angle of preoperative esotropia increased with age. The postoperative esotropia was 8.7° ± 9.9°, and six patients were overcorrected. While preoperative esotropia was highly associated with postoperative results, we found no association of additional MRR with any of our postoperative outcome measures. The Yokoyama procedure had a higher absolute effect in patients with higher preoperative esotropia. Conclusion: Our study confirms the positive effect of the Yokoyama procedure on strabismus due to high myopia in large‐scale real‐world data. In some cases, MRR may be needed because of muscle contracture, although additional MRR statistically did not affect the postoperative outcome. In patients with bilateral high myopic strabismus, correction of both eyes seems beneficial. The effect size of the Yokoyama procedure appears to be mainly driven by preoperative esotropia.